Pelatihan Pembelajaran Aplikasi Cerdas Cermat Unik (ACCU) Bagi Para Siswa SDN Pabean 1 Sedati Sidoarjo - Titus Kristanto; Rachman Arief (Universitas Tribhuwana Tunggadewi Malang, 2019)
Education is a process to mature someone from various sectors. Education can be taken from various processes both formal, informal and non-formal education. At the age of children 0-6 years, is the right period of the child's brain is growing rapidly. So that it can absorb quickly both heard and seen. Based on data from the Education Authorities, the results of the National Examination for elementary school have decreased compared to previous years. The decline in the value of the National Examination is caused by students being less interested in learning. In order for students to be interested in learning, innovation is needed in the form of educational games as learning media. The educational game is intended for grade VI elementary school students to face the National Examination. The result of making educational games is that students are more comfortable playing games while learning, so they can add insight and knowledge, and strengthen student's memory.ABSTRAK Pendidikan merupakan proses untuk mendewasakan seseorang dari berbagai sektor. Pendidikan dapat ditempuh dari berbagai proses baik pendidikan formal, informal, maupun non-formal. Pada usia anak 0-6 tahun, merupakan periode yang tepat otak anak sedang berkembang dengan pesat. Sehingga dapat menyerap secara cepat baik yang didengar maupun yang dilihat. Berdasarkan data dari Dinas Pendidikan, hasil nilai Ujian Nasional untuk jenjang SD mengalami penurunan dibandingkan dengan tahun-tahun sebelumnya. Penurunan nilai Ujian Nasional disebabkan siswa kurang tertarik untuk belajar. Supaya siswa tertarik untuk belajar, diperlukan inovasi berupa game edukasi sebagai media pembelajaran. Game edukasi tersebut ditujukan bagi para siswa kelas VI SD untuk menghadapi Ujian Nasional. Hasil dari pembuatan game edukasi adalah para siswa agar lebih nyaman bermain game sambil belajar, sehingga dapat menambah wawasan dan pengetahuan, serta memperkuat daya ingat siswa.Kata kunci : game edukasi; pendidikan; ujian nasional; siswa SD